THE SYMBOLIC MEANING OF GAMA’ TRADITION IN MONGONDOW TRIBE WEDDING - Humaira, Talitha; Parani, Rizaldi (Jurnal Lectura, 2025)
This research aims to uncover the symbolic meaning and social function of the Gama' traditional wedding ritual of the Mongondow tribe. The Gama' tradition is the final stage of a series of wedding rituals that must be performed, encompassing 13 stages rich in symbolism and cultural values. This study uses a qualitative approach with ethnographic methods to gain an in-depth understanding of this ritual through in-depth interviews, participant observation, and literature review. The main informants consist of the head of the cultural heritage institution, traditional elders, and community members involved in the execution of the traditional ceremony. The results show that each stage in the Gama' tradition has symbolic meaning reflecting the ancestral, religious, moral, social, and ethical values of the Mongondow community. The study also found that despite the influence of modernization causing changes in the ritual's execution, the essence and symbolic meaning of the Gama' tradition are maintained. Gama' plays a crucial role in strengthening the cultural identity and social bonds of the Mongondow community, providing guidance for the younger generation in understanding and preserving their cultural heritage.